Chemical Characteristics and Trends of Indian Summer Monsoon Rainfall: A Review - Aditi Majumdar; Dhrubajyoti Samanta; Reshmi Das (Aerosol and Air Quality Research)
Abstract The Indian summer monsoon (ISM) regulates the pace of life for billions of people in the Indian subcontinent by driving the agriculture and Gross Domestic Product of the region. The chemical composition of ISM is influenced by pollutant type, meteorology, and topography. As a result, the chemical makeup of rainwater varies greatly across places. The current review article highlights the variations and trends of the principal chemical constituents of rainwater (Na+, K+, Ca2+, Mg2+, NH4+, NO3–, SO42–, and Cl–) across six homogeneous Indian monsoon regions: Central Northeast, Hilly, Northwest, Northeast, Peninsular and West Central region. Average rainwater pH ranged from 5.31 to 6.70 in these six regions. The incidence of acidic rain events at three separate locations in the Peninsular region suggests a significant impact of anthropogenic emissions. The chemical composition of rainwater in all these regions varied considerably and seemed to form a regional pattern. The majority of the ions in rainwater were highest in the Northwest while lowest in the Peninsular region. Cl– had a significant correlation with Na+ and NH4+ in the Hilly region, and with Na+ and Mg2+ in the West Central region suggesting it is sourced from both marine and anthropogenic sources. The soil Enrichment Factor relative to Ca2+ demonstrated that soil has a significant effect on rainwater composition. Ca2+ was determined to be the most abundant neutralizing ion in all the regions. Furthermore, the synthesis of rainwater chemistry reveals a strong relationship with dominant interannual climate variability El Niño Southern Oscillation with significantly higher concentrations of Na+, K+, Ca2+, Cl–, and SO4– in rainwater during El Niño year compared to La Niña year.